PERBEDAAN PENGARUH TEKNIK MARMET DENGAN PIJAT OKSITOSIN TERHADAP PRODUKSI ASI IBU POSTPARTUM DI RUMAH SAKIT IBU DAN ANAK IBI SURABAYA - setiawandari, setiawandari (EMBRIO, 2015)
This research is motivated by the decrease of breast milk production of postpartum mother in the early breast feeding process that become a problem for mother to provide breast milk early on her baby. The delay of breast milk production could be stimulated by the use of intervention of mamet technique and oxytocin massage. This study aims to understand the difference between the influence of mamet technique and oxcytocin massage toward the production of breast milk of the postpartum mother in RSIA IBI Surabaya. This research is an experiment study using pre and post test only design with control group. Using a total sample technique, this research was conducted toward 40 postpartum mothers. The technique of data analysis applied in this study is normality data test, t-pair test, and t-independent test. The result of this research shows that there has been an influenced of mamet technique toward the production of breast milk of those postpartum mothers p=0,000 and there has been influenced of oxytocin massage toward the production of breast milk of those postpartum mothers p=0,000. There is no difference influence between mamet technique and oxytocin massage toward the production of breast milk of the postpartum mothers p=0,893. Based on the result, it can be concluded that: (1) mamet technique has increased the production of breast milk of the postpartum mother; (2) oxytocin massage has increased the production of breast milk of the postpartum mother; (3) there is no difference influence between mamet technique and oxytocin massage in increasing the production of breast milk of the postpartum mother in RSIA IBI Surabaya